2015
DOI: 10.1016/j.celrep.2015.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Elephantid Genomes Reveal the Molecular Bases of Woolly Mammoth Adaptations to the Arctic

Abstract: Woolly mammoths and living elephants are characterized by major phenotypic differences that have allowed them to live in very different environments. To identify the genetic changes that underlie the suite of woolly mammoth adaptations to extreme cold, we sequenced the nuclear genome from three Asian elephants and two woolly mammoths, and we identified and functionally annotated genetic changes unique to woolly mammoths. We found that genes with mammoth-specific amino acid changes are enriched in functions rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 85 publications
6
108
1
1
Order By: Relevance
“…Numerous genes involved in glucose metabolism indicated that sugar-related antifreezing properties and the ability to regulate seasonal thermogenic requirements might also be essential to survive the Arctic cold. Interestingly, the biological significance of some of these candidates was corroborated in woolly mammoths (Lynch et al 2015), where parallel episodes of positive selection have been described at the BARX2 and PHIP genes, associated with hair development and insulin metabolism, respectively. Similarly, human groups from Siberia (Cardona et al 2014) also show adaptive footprints at the PRKG1 gene, which participates in shivering by regulating blood vessel constriction.…”
Section: Engendering Modern Breedsmentioning
confidence: 88%
“…Numerous genes involved in glucose metabolism indicated that sugar-related antifreezing properties and the ability to regulate seasonal thermogenic requirements might also be essential to survive the Arctic cold. Interestingly, the biological significance of some of these candidates was corroborated in woolly mammoths (Lynch et al 2015), where parallel episodes of positive selection have been described at the BARX2 and PHIP genes, associated with hair development and insulin metabolism, respectively. Similarly, human groups from Siberia (Cardona et al 2014) also show adaptive footprints at the PRKG1 gene, which participates in shivering by regulating blood vessel constriction.…”
Section: Engendering Modern Breedsmentioning
confidence: 88%
“…There were stretches of high conservation in these sequences at the amino acid level between all species; third base codon degeneracy was often present but not great enough to prevent seed mapping of reads (using standard, default alignment criteria). The same forced mapping was then performed using DNA sequencing of an extinct organism (representing some of the oldest DNA available to us), the woolly mammoth (Lynch et al, 2015), where three of the five ubiquitous genes with regions of high conservation also mismapped. As the number of Salix genes hosting reads from each organism (mapped independently) was relatively small, such commonality is rather surprising.…”
Section: Forced Mappingmentioning
confidence: 99%
“…Возможность использования ДНК из археологического и палеонтологического материала позволяет решать многочисленные задачи, связанные с эволюцией экосистем в различных климатических условиях, с происхождением и эволюцией многих патогенных микроорганизмов, например чумной палочки, возбудителей туберкулеза или бруцеллеза [12]. В данной работе использовались геномные чтения шерстистого мамонта (Mammuthus primigenius), опубликованные ранее [13].…”
Section: Introductionunclassified